2011
DOI: 10.3892/ijo.2011.1230
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP-kinase by AICAR induces apoptosis of DU-145 prostate cancer cells through generation of reactive oxygen species and activation of c-Jun N-terminal kinase

Abstract: Abstract. The growth of cancer cells is limited by energy supply which is regulated by the energy sensor AMP-kinase (AMPK). Hence, mimicking a low energy state may inhibit cancer growth and may be exploited in anticancer therapies. In the present study, the impact of AMPK activation on cell growth and apoptosis of DU-145 prostate cancer cells was investigated. Incubation with the AMPK activator aminoimidazole carboxamide ribonucleotide (AICAR) dose-dependently inhibited cell growth, activated AMPK, and inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Among the signaling pathways regulated by AMPK, mTOR is known to perform a central role in antitumor activity (23). Recently, several compounds, including metformin and myrtucommulone A, have been reported to exert antileukemia activity via activation of the AMPK/mTOR signaling pathway (24,25). Similarly, the present results revealed that adenine suppressed the viability of K562 cells through activation of the AMPK/mTOR signaling pathway, resulting in G 2 /M phase arrest and autophagic cell death.…”
Section: Discussionsupporting
confidence: 66%
“…Among the signaling pathways regulated by AMPK, mTOR is known to perform a central role in antitumor activity (23). Recently, several compounds, including metformin and myrtucommulone A, have been reported to exert antileukemia activity via activation of the AMPK/mTOR signaling pathway (24,25). Similarly, the present results revealed that adenine suppressed the viability of K562 cells through activation of the AMPK/mTOR signaling pathway, resulting in G 2 /M phase arrest and autophagic cell death.…”
Section: Discussionsupporting
confidence: 66%
“…The apoptosis induced by Orlistat and AICAR co-treatment is preceded by an increase in ROS production and caspase 9 and 3 activation (Figure 4). AICAR has been reported to inhibit cell growth and induce apoptosis in DU145 PCa cells in a ROS and caspase 3-dependent manner [Sauer et al, 2012]. AICAR has also been implicated in the potentiation of ROS production induced by high glucose levels in pancreatic beta cells [Kim et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, pharmacologic activation of AMPK has been reported to decrease growth and viability of several prostate cancer cell lines in vitro and to inhibit lipid synthesis induced by the synthetic androgen R1881 [26]. Multiple mechanisms may contribute to these effects of AMPK, including inhibition of the mTOR pathway, up-regulation of p53 and p21 [27] and induction of apoptosis through generation of reactive oxygen species as well as through cross-talk with TNF signalling [28, 29]. In addition to its anti-proliferative effects, AMPK may also enhance the sensitivity of cancer cells to therapeutic treatments.…”
Section: Introductionmentioning
confidence: 99%